2008
DOI: 10.1021/bi702200m
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Mapping of the Sugar Interactions in One-Site and Two-Site Mutants of Cyanovirin-N by NMR Spectroscopy

Abstract: The details of the interaction between two mutants of Cyanovirin-N (CV-N), an HIV inactivating protein, and di- and trimannosides, substructures of Man-9, were investigated by STD NMR spectroscopy. One mutant, CV-N (mutDB), contains only one carbohydrate-binding site on domain A, whereas in CV-N (mutDA), the specificity of domain A for trimannose was changed while the site in domain B was kept intact, allowing for a dissection of the overall binding. Results of the STD NMR experiments revealed close contact be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 38 publications
2
20
0
Order By: Relevance
“…4245 We compared the dynamic information retrieved from 1 ns to 400 ns MD runs. As depicted in the Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4245 We compared the dynamic information retrieved from 1 ns to 400 ns MD runs. As depicted in the Fig.…”
Section: Resultsmentioning
confidence: 99%
“…18,19 Earlier STD NMR studies with Man 3 resulted in low STD signals, 20 and STD NMR with Man 3 for single binding site mutants did not yield STD signals because the off-rate was too small. 21 NMR studies on a 19 F-labeled Man 3 revealed a single binding mode on domain A, but two binding modes in the binding site of domain B. 22 Previous work on CV-N mannose binding primarily used the disaccharide Manα(1–2)Manα.…”
Section: Introductionmentioning
confidence: 99%
“…[34] These results prompted us to proceed to studying the interaction with the lectin by 19 F-NMR spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…[28,31,32] The availability of detailed STD data for these ligands as well as results with specific deoxy sugars allowed us to identify the pivotal hydroxyl groups responsible for binding. [33,34] In particular, we determined that the 3′- and 4′-hydroxyl groups are essential for the interaction, whereas the 2′- and 6′-hydroxyl groups of the Manα(1–2)Manα (Man2) terminal unit are not directly involved in CV-N binding. [34] We therefore prepared methyl 2-deoxy-2-fluoro-α-D-mannopyranosyl-(1→2)-α-D-mannopyranoside ( 19 F-Manα(1–2)Manα: 19 F-Man2) and methyl 2-deoxy-2-fluoro-α-D-mannopyranosyl-(1→2)-α-D-mannopyranosyl-(1→2)-α-D-mannopyranoside ( 19 F-Manα(1–2)Manα(1–2)Manα: 19 F-Man3) (Supplementary Scheme S1) for use in our current work.…”
Section: Introductionmentioning
confidence: 99%